The modular expression patterns of three pigmentation genes prefigure unique abdominal morphologies seen among three Drosophila species - Dion, William A. (Gene Expr Patterns, 2020)
To understand how novel animal body colorations emerged, one needs to ask how the development of color patterns differs among closely related species. Here we examine three species of fruit flies – Drosophila guttifera (D. guttifera), D. palustris, and D. subpalustris – displaying a varying number of abdominal spot rows. Through in situ hybridization experiments, we examine the mRNA expression patterns for the pigmentation genes Dopa decarboxylase (Ddc), tan (t), and yellow (y) during pupal development. Our results show that Ddc, t, and y are co-expressed in modular, identical patterns, each foreshadowing the adult abdominal spots in D. guttifera, D. palustris, and D. subpalustris. We suggest that differences in the expression patterns of these three genes partially underlie the morphological diversity of the quinaria species group.